Incremental Development of Safety Cases: A Mapping Study - Almendra, Camilo; Silva, Carla; Vilela, Jéssyka (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2020)
Context: Safety assurance case (SAC) development is an approach for discussing, analysing and assessing the safety properties of systems before a certification procedure. Late development of SACs lead to late discovery of hazards, risks, requirement and design issues that affect safety of the systems. Also, increased rework to recall safety evidence information impact project schedules and costs. However, it is still challenging to develop SACs incrementally. Objective: We aim to identify and analyse existing approaches for integrating SAC development as part of the software development processes in an incremental manner and an analysis of such approaches in terms of how the integration with existing processes occurs, which are the roles involved and which are the expected outcomes. Method: We performed a Systematic Mapping Study to identify and analyse the existing approaches for incremental SAC development. We identified 16 peer-reviewed studies from a set of 1242 studies published until January 2020. Results: We developed a classification for the approaches using three aspects: life cycle model, task integration and argument development. We also found that development-related roles are gaining importance in the construction and review of SACs. Finally, we identified the expected outcomes when adopting incremental development of SACs. Conclusions: The analysis presented in this paper can help practitioners to understand the SAC development area better, and to choose how to adopt incremental SAC development into their processes. Also, we present research directions for further work on the topic.